Convertible bonds : the low-risk, high-profit alternative to buying stocks - Noddings, Thomas C. (London : McGraw-Hill Book Co., 1991)
Convertible bonds introduce readers to a high-performance/low-risk investment program using overlooked alternatives to traditional stocks, bonds and money market instruments.
Rev. ed. of: Low-risk strategies for the high-performance investor. 1985.
Includes bibliographical footnotes and index.
ne 31/01/2019
Loans
Keywords: Investments--Bonds.; Convertible bonds